2014
DOI: 10.11606/issn.2357-8041.v20i1p16-22
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PCNA, p53 and Ki-67 in dentinogenic ghost cell tumors and calcifying cystic odontogenic tumors

Abstract: The aim of this study was to compare the proliferative pattern of dentinogenic ghost cell tumors (DGCT) and unicystic calcifying cystic odontogenic tumors (UCCOT) using antibodies against PCNA, p53 and Ki-67. Three cases diagnosed as DGCT and ten as UCCOT were retrieved from the fi les of the Surgical Oral Pathology Service at the University of São Paulo, Brazil. Immunohistochemistry was performed in formalin-fi xed and paraffi n-embedded tissue specimens. Only nuclear staining was considered specifi c for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The available literature to the best of our knowledge revealed that only 88 cases have been reported and published from 1968 till date. [ 3 4 5 6 ] Herewith, we report a case of central DGCT in a 68-year-old male patient with clinical presentation as a soft tissue growth over alveolar ridge.…”
Section: Introductionmentioning
confidence: 99%
“…The available literature to the best of our knowledge revealed that only 88 cases have been reported and published from 1968 till date. [ 3 4 5 6 ] Herewith, we report a case of central DGCT in a 68-year-old male patient with clinical presentation as a soft tissue growth over alveolar ridge.…”
Section: Introductionmentioning
confidence: 99%